Long-term risk of de novo malignancy with tumor necrosis factor alpha (TNF) inhibitor immunosuppression: a multicenter, retrospective cohort study - Conor B. Driscoll; Jordan M. Rich; Christopher Yang; Joseph Nicolas; Dylan Isaacson; Philip Silberman; Xinlei Mi; Sai Kaushik Shakar Ramesh Kumar; Hui Zhang; Steven Belknap; William H. Temps; Edward M. Schaeffer; et al. (Journal of Inflammation)
Abstract Background Tumor necrosis factor-alpha (TNF) is an inflammatory cytokine implicated in the development of many chronic inflammatory diseases and TNF-α inhibitors (TNF-I) are frequently prescribed as treatment. Their malignancy risk is debated, with pro-oncogenic effects of decreased immune surveillance and anti-oncogenic effects of decreasing chronic inflammation. As such, the literature is inconclusive in the malignancy risk of these medications. Here we investigate the malignancy risk in patients with chronic TNF-I exposure. Methods This is a single health system, retrospective non-matched cohort study of patients with chronic inflammatory conditions between 1996 and 2023. Patients exposed to TNF-I were identified using the generic medication names and the chronic inflammatory disease indication. The unmatched control cohort consisted of patients with the same chronic inflammatory conditions but without TNF-I exposure. Malignancies in this population were identified using ICD-9 and ICD-10 codes. TNF-I exposure was analyzed as a time-varying covariate prior to model fitting. Hazard ratios (HR) for TNF-I exposure on overall and individual cancer risk were estimated using two-sided Cox proportional hazards regression. Results There were 12,941 patients exposed to TNF-I and 37,402 patients unexposed to TNF-I. TNF-I exposure was not associated with overall cancer risk (HR 1.05, 95% CI 0.92–1.19). TNF-I exposure was positively associated with melanoma (HR 1.45, 95% CI 1.01–2.08), basal cell carcinoma (BCC) (HR 1.6, 95% CI 1.18–2.15) and squamous cell carcinoma (SCC) (HR 1.8, 95% CI 1.15–2.83), and negatively associated with prostate cancer (PCa) (HR = 0.51, 95% CI 0.29–0.91), leukemia (HR 0.12, 95% CI 0.02–0.83), and non-Hodgkin lymphoma (NHL) (HR 0.36, 95% CI 0.13–0.98). There was an increased risk of overall malignancy in TNF-I exposed patients with Psoriasis (HR 1.53, 95% CI 1.15–2.03, p = 0.003) but not in other inflammatory conditions. Conclusions Patients with TNF-I exposure had higher risk of melanoma, skin SCC and BCC along with lower risk of leukemia, NHL, and PCa. This is consistent with previous melanoma, skin SCC and BCC data and demonstrates novel findings for leukemia, NHL, and PCa. There may need to be differential cancer screening algorithms for patients with different inflammatory conditions and TNF-I exposure.